(untitled) (Eurasian Scientific Herald, 2022)
The article in the organs of internal affairs of the republic of Uzbekistan concerning the development of bilateral relations review some of the readers in the example of Fergana region police office was the analysis. Additionally, the article in fergana region police office in the city and district of the republic of uzbekistan ministry of internal affairs of the 400 year 2021 October 21-number of command for the execution of works was the discussion of results